Entre a submissão e a rebeldia – o retrato da mulher moçambicana em “Balada de amor ao Vento” de Paulina Chiziane - Renata, Díaz-Szmidt (Wydawnictwo Naukowe UAM, 2013)
The purpose of this article is to analyze the psychological stance of Sarnau, the main character of the novel "Ballad of Love in The Wind" of the Mozambican writer Paulina Chiziane. The writer describes the Mozambique of today, which is divided into tradition and modern life, ancestral and native way of life. The analysis of the novel shows that Paulina Chiziane breaks the stereotyped image of the woman by representing her as a being aware of her inferior social situation and as a being who intends to oppose the sexist and patriarchal society. Sarnau must face up to the cultural clash resulting from the encounter between the Western and African cultures. She lives in a polygamous family and has to find her place within this family and within the society. Chiziane’s protagonist tries to change her situation in order to find her identity as a women, mother and African wife.
Between submissiveness and rebelliousness – image of the Mozambican woman in Paulina Chiziane’s "Ballad of Love in the Wind"
Keywords: literature of Mozambique; patriarchal society; Paulina Chiziane; tradition; women